2018
DOI: 10.1002/app.46606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of phthalonitrile terminated polyaryl ether nitrile containing fluorene group

Abstract: A series of phthalonitrile terminated polyaryl ether nitrile oligomers containing fluorene group (BPPENs) were synthesized and cured in the presence of bis[4‐(4‐aminophenoxy)phenyl]sulfone. Additionally, the quartz fiber reinforced composites were prepared by hot‐pressing process. The structure of oligomers was characterized by 1H‐NMR and GPC. The curing behavior of BPPENs was studied by DSC, IR, and rheological tests in detail. Thermal stability and mechanical properties were also investigated. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…BPPEN was prepared according to our previous publication and characterized by using hydrogen nuclear magnetic resonance ( 1 H NMR), FTIR, and GPC. 26 Based on the previous studies, BPPEN with an average molecular weight of 4500 ( M w ) was selected as the modifier used in this work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BPPEN was prepared according to our previous publication and characterized by using hydrogen nuclear magnetic resonance ( 1 H NMR), FTIR, and GPC. 26 Based on the previous studies, BPPEN with an average molecular weight of 4500 ( M w ) was selected as the modifier used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon demonstrated that, within 15 wt%, BPPEN had limited impact on the rheological behavior of the blends, despite BPPEN itself possessed very high viscosity as reported in previous work. 26 And the low viscosity values of BPAPNs made these resins suitable for liquid composite fabrication process, such as resin transfer molding. 4 The viscosity of blends started to increase sharply around 280-310 C, which convinced the cross-linking reaction of the resins in the presence of amine catalyst.…”
Section: Processabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] This promoted the development of PN resin, 9,11 which has happened rapidly over the past 20 years. [12][13][14][15][16][17][18] Among these PN catalysts, the catalysts containing -NH 2 have the highest outstanding catalytic performance and have been widely used, [19][20][21][22][23][24] such as p-BAPS, 25 m-APB, 26 4-APN, 5 etc. (shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(arylene ether nitrile)‐phenyl (PEN‐Ph) as a kind of high‐performance engineering plastics is usually a linear polymer, and it is widely used in the commercial and academic fields due to its excellent performance such as outstanding chemical properties (radiation resistance, low flammability, and toxic gas emission), high thermal stability, superior mechanical properties as well as good molding workability . The PEN with different dihydric phenol structure (Figure ) possesses different properties.…”
Section: Introductionmentioning
confidence: 99%